Nonlinear Simulation and Optimization of Oil Palm Bunch Stripping Machine - Onwukwe, M.C.; Nwankwojike, B.N.; Edeh, John Chijioke (Kathmandu University Journal of Science, Engineering and Technology, 2020)
A developed oil palm stripping machine was evaluated, optimizing its performance in oil palm bunch stripping. The operational parameters considered were the rotary speed of the machine, mass of loaded oil palm, length of the stripping shaft, number of beaters, and stripping time, while the stripping efficiency, throughput capacity, and specific energy consumption of the machine constituted performance parameters. A two-level half factorial central composite design was employed in the development of empirically based nonlinear models for predicting the performance responses. The developed models were used to optimize the performance using the MOSQP solver for nonlinear programming. It was established that the optimal factor settings of the machine were 438rpm, 45kg, 2625mm, 8 beaters, and 540 seconds for the machine speed, mass of loaded palm bunch, shaft length, number of beaters, and stripping time, respectively. The optimal performances at these factor settings were 84.2%, 225kg/hr, and 57.51kJ/kg at an optimality rate of 91%, 99.1%, and 97.2% for the stripping efficiency, throughput capacity, and specific energy consumption, respectively, with an overall optimality value of 95%. Also, confirmatory test results showed that the machine, when operated at the optimal settings, gave values close to the predicted optimal results at a 95% confidence level. With these models, oil palm bunch stripping machines were characterized and rated for increased productivity and earnings in the oil palm processing sector.